Предмет: Алгебра,
автор: halwa23
Произведение корней уравнения (2x + 8)^2 (13х – 39) = 26(4x^2 — 64)(х-3)
равно
Ответы
Автор ответа:
1
Ответ:
х1= -4 х2=3 х3=12
Объяснение:
(2x + 8)^2 (13х – 39) = 26(4x^2 — 64)(х-3)
(4+32+64)(13x-39) = (104
-1664)(х-3)
54-156
+416
-1248x-832x-2496 = 104
-312
-1664x+4992
54+260
-416x-2496 = 104
-312
-1664x+4992
+5
-8x-48 = 2
-6
-32x+96
+5
-8x-48-2
+6
+32x-96 = 0
-+11
+24x-144 = 0
-+3
+8
-24x+48x-144 = 0
-(x-3)+8x(x-3)+48(x-3) = 0
-(x-3)(-8x-48) = 0
-(x-3)(-4x-12x-48) = 0
-(x-3)(x(x+4)-12(x-4)) = 0
-(x-3)(x-4)(x-12) = 0
(x-3)(x-4)(x-12) = 0
x-3 = 0
x+4 = 0
x-12 = 0
x =3
x =-4
x =2
Ответ:
=3
= -4
=12
Похожие вопросы
Предмет: Английский язык,
автор: liza348
Предмет: Українська мова,
автор: katiolsh
Предмет: Другие предметы,
автор: Аноним
Предмет: Математика,
автор: алсу141
Предмет: Математика,
автор: неодекватномер11